1987
DOI: 10.1007/bf00444952
|View full text |Cite
|
Sign up to set email alerts
|

Down syndrome and leukemia: unusual clinical aspects and unexpected methotrexate sensitivity

Abstract: Twenty-four patients with Down syndrome and leukemia were studied. A strong male predominance (79%) was found. Age ranged between 18 months and 15 years (mean: 5 6/12); 54% of the patients were less than 4 years of age at the time of diagnosis. A preleukemic phase was noted in 6/24 patients. This phase, characterized essentially by thrombocytopenia, lasted from 2-8 months. Patients with preleukemia had unusual blast cell morphology and involvement of more than one cell line (dyserythropoiesis, hypolobulated me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
47
0
3

Year Published

1990
1990
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(51 citation statements)
references
References 32 publications
1
47
0
3
Order By: Relevance
“…2,16,24 In our study, a significantly higher proportion of children with DS experienced methotrexate-induced gastrointestinal toxicity compared with the non-DS controls, which is consistent with other reports. 2,16,24,25 Dose reductions were applied both in anticipation of possible toxicity, and because of apparent excessive toxicity, and were restricted to DS patients only. However, due to excessive toxicity both DS-ALL patients (n=3) and one non-DS-ALL patient, each received one course less than required per protocol.…”
Section: Discussionsupporting
confidence: 82%
“…2,16,24 In our study, a significantly higher proportion of children with DS experienced methotrexate-induced gastrointestinal toxicity compared with the non-DS controls, which is consistent with other reports. 2,16,24,25 Dose reductions were applied both in anticipation of possible toxicity, and because of apparent excessive toxicity, and were restricted to DS patients only. However, due to excessive toxicity both DS-ALL patients (n=3) and one non-DS-ALL patient, each received one course less than required per protocol.…”
Section: Discussionsupporting
confidence: 82%
“…3 As in the present study, the majority of other investigators reported an unusual increased MTX toxicity in DS patients. [3][4][5]6,8,9,11,12 One pharmacokinetic study in patients with DS showed a slower than expected intracellular clearance of methotexate (1 g/m 2 ) and significant increased toxicity in comparison to other children with ALL. 12 In the present study, total duration of therapy with 18 vs 24 months in trials ALL-BFM 81 and 83 had no significant influence for outcome in DS patients.…”
Section: Figurementioning
confidence: 99%
“…In contrast, survival rates for DS patients were inferior in most studies but ranged between 23 and 71%. [4][5][6][7][8][9][10][11][12] The inferior outcome was mainly attributed to excessive therapy-related toxicities caused either by altered drug metabolism and/or poor tolerance of infection and therefore, less treatment intensity. Authors from the Pediatric Oncology Group found the event-free survival (EFS) for children with DS and ALL with 50% similar to other children with ALL, once they received intensive chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…A number of such reported cases exhibited a preleukemic phase, characterized by thrombocytopenia (Beven and Rose 1982;Hayashi et al 1986;Peeters and Poon 1987), but the etiology of thrombocytopenia has been unknown. We describe a case of AMKL in a boy with Down syndrome, following thrombocytopenia with antiplatelet antibody.…”
mentioning
confidence: 99%
“…Though he received chemotherapy, he expired 4 months after admission. A number of reported cases of AMKL with Down syndrome exhibit a preleukemic phase, characterized by thrombocytopenia (Beven and Rose 1982 ;Hayashi et al 1986;Peeters and Poon 1987). The patients in this phase were diagnosed as having ITP, preleukemia or refractory anemia with excess of blasts.…”
mentioning
confidence: 99%